The Impact of Agricultural Modernization on Human Resource Regeneration in Cianjur Regency: The Role of Youth Interest as a Mediating Variable - Kartini, Iis; Hilmiana; Nidar, Sulaeman Rahman (Yayasan Sinergi Kawula Muda, 2025)
Agriculture in Indonesia faces a human resource regeneration crisis as fewer young people enter the sector. This study examines how agricultural modernization can attract the younger generation back to agriculture and how youth interest functions as a mediating factor in accelerating this regeneration process. The research method used is a quantitative approach with a survey design. The sample consists of 50 farmers and agricultural workers, divided into two groups: those who have adopted modern agricultural technology and those using traditional techniques. The results show that agricultural modernization has a significant positive impact on human resource (HR) regeneration, with the interest of the younger generation acting as a mediator that strengthens this relationship